Exploring a qualitative methods approach to measure learning gain in teaching assistants: a Chinese case study / Jianmei Xie and Henk Huijser - Xie, Jianmei; Huijser, Henk (Universiti Teknologi MARA, 2020)
This paper explores the use of a range of qualitative methods to measure learning gain of teaching assistants (TAs) in mainland China at a Sino-British University where the authors used to work. It uses a case study to report on an evaluation of TA training at the University, which is part of its Postgraduate Research Development Programme, to ascertain students’ acquired skills and skills gaps. A key focus of this evaluation consists of exploring ways to measure learning gain for individual TAs. As teacher educators, the researchers delivered TA training, conducted specialist observations of TAs’ teaching practice, as well as a series of ‘Learning to Teach’ groups. Measuring individual learning gain of TAs occurred during the semester and at the end of the semester. Criteria and measurements were tested to explore how learning gain of TAs could be measured in a Chinese higher education context. Implications outlined in this paper could be useful for TA training in higher education settings. Key findings include that evaluation of learning gain should occur at different points in time, as well as be continuous, consistent and comprehensive. In other words, multiple approaches, including both quantitative and qualitative methods, could capture a more objective picture of TAs’ learning gains.